2010
DOI: 10.2478/s11696-010-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of brushite nanoparticles at different temperatures

Abstract: Phase pure, stable nanocrystalline brushite particles with average diameter in the range of 23–87 nm were obtained by the reverse microemulsion technique employing a mixture of surfactants (Aliquat 336 & Tween 80) as template directing agents, and calcium nitrate tetrahydrate and biammonium hydrogen phosphate as precursors. Particle sizes and morphologies were tuned by adjusting the reaction parameters, precursor concentration and temperature. FTIR, TEM, and XRD were used to characterize morphological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 34 publications
4
21
0
2
Order By: Relevance
“…For example, several authors have reported the production of spherical CaP particles with a diameter close to 15–20 nm, either by precipitation, 47 - 49 precipitation-emulsification, 50 , 51 spray-drying, 52 and flame-synthesis ( = flame pyrolysis) 53 - 55 (Table 2). The solutions may be either aqueous (precipitation, spray-drying), non-aqueous (precipitation, 56 flame-synthesis 57 - 60 ) or a mixture thereof (precipitation-emulsification 50 , 51 , 61 ). …”
Section: Methods To Produce Spherical Cap Particlesmentioning
confidence: 99%
“…For example, several authors have reported the production of spherical CaP particles with a diameter close to 15–20 nm, either by precipitation, 47 - 49 precipitation-emulsification, 50 , 51 spray-drying, 52 and flame-synthesis ( = flame pyrolysis) 53 - 55 (Table 2). The solutions may be either aqueous (precipitation, spray-drying), non-aqueous (precipitation, 56 flame-synthesis 57 - 60 ) or a mixture thereof (precipitation-emulsification 50 , 51 , 61 ). …”
Section: Methods To Produce Spherical Cap Particlesmentioning
confidence: 99%
“…; monotite (DCPA) and brushite. A band at 989 cm -1 is assigned from the P-O(H) symmetric stretching vibration of PO 4 3-group (Singh et al 2010;Maity et al 2011). Moreover, band near to 1064 cm -1 is reffered to the m 3 stretching mode of the PO 4 3-group.…”
Section: Ftir Analysismentioning
confidence: 99%
“…The bands at 3166, 3287, 3489 and 3542 cm -1 corresponded to stretching vibration of water [m s (O-H)] (Singh et al 2010;Ahmed et al 2014). The bands between 3000 and 3600 cm -1 show the presence of DCPD but not in its anhydrous form DCPA (Singh et al 2010;Zou et al 2012).…”
Section: Ftir Analysismentioning
confidence: 99%
See 2 more Smart Citations